Unique continuation for fractional Schrödinger equations with rough potentials - Rüland, Angkana (Communications in partial differential equations, 2015)
This article deals with the weak and strong unique continuation principle for fractional Schrödinger equations with scaling-critical and rough potentials via Carleman estimates. Our methods extend to “variable coefficient” versions of fractional Schrödinger equations and operators on non-flat domains.
Published online: 14 Oct 2014
Gesehen am 27.05.2021